Modified perfluoroethylene-propylene copolymer composition as well as preparation method and application thereof
By mixing FEP dispersions of different particle sizes and polyurethane dispersions to form a modified FEP composition, the problems of insufficient stability and coating performance of the FEP dispersion in the prior art are solved, and excellent bonding strength and coating density with the polyimide substrate are achieved.
Patent Information
- Application Number
- CN202411716856.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the FEP dispersion has low stability and poor coating performance, resulting in insufficient bonding strength with the polyimide substrate and uneven coating.
By mixing the first perfluoroethylene propylene copolymer dispersion, the second perfluoroethylene propylene copolymer dispersion and the polyurethane dispersion, a modified perfluoroethylene propylene copolymer composition is formed for preparing a modified FEP composition with excellent stability and applied on the surface of the polyimide film or sheet to improve the adhesive strength and coating density.
The excellent stability and excellent adhesive strength of the modified FEP composition are achieved, the denseness and uniformity of the coating are ensured, and the problems of insufficient stability and coating performance of the FEP dispersion in the prior art are solved.
Smart Images

Figure CN119529508A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical industry, and in particular to a modified perfluoroethylene-propylene copolymer composition having improved bonding strength and coating performance for polyimide, a preparation method of the composition and application thereof. Background Art
[0002] Polyimide (hereinafter referred to as PI) is an organic polymer material with excellent comprehensive properties, and has a wide range of applications and uses, such as being used in various electrical equipment, electronic equipment, solar cells, aerospace, insulation-insulation-fireproof materials, gas separation, chemical environmental protection, etc. in the form of thin films, fibers or other forms. In these uses, for various purposes (such as providing mechanical protection, improving heat resistance, chemical corrosion resistance, weather resistance, yellowing resistance, biocompatibility, anti-sticking, etc.), it is often necessary to apply a perfluoroethylene propylene copolymer (FEP) coating or adhesive on one or more surfaces of a polyimide profile (such as a film or sheet) to form a laminate with a double-layer or more layer structure. For example, a conventional method for coating a FEP coating on a polyimide film is to immerse the polyimide film in a tank filled with FEP coating, and then dry or sinter after immersion coating to obtain a polyimide film with a FEP coating on the surface.
[0003] However, the FEP coatings or adhesives commonly used in the prior art always have serious problems when used in combination with various polyimide substrates. The first problem is that the stability of the FEP dispersions (e.g., emulsions) in the prior art is relatively low, and flocculation and precipitation may occur after a period of storage. The second problem is that the coating performance of the FEP dispersions in the prior art is poor, and it is easy to produce a non-dense or non-uniform film layer during the application-drying-sintering process, and the bonding strength between the FEP dispersions and the polyimide is insufficient.
[0004] The above-mentioned serious defects of the prior art have formed a huge contradiction with the growing demand in the field for various products with high performance and high quality having a PI / FEP laminated structure. People are eager to develop a new technology that can solve the above-mentioned problems.
[0005] In order to solve this urgent problem, the applicant has conducted a lot of in-depth research and unexpectedly found that the specially designed process of the present invention can be used to simply and inexpensively prepare a modified FEP composition with excellent stability, and when the modified FEP composition is applied to the surface of a PI film or sheet, it can achieve excellent bonding strength and a dense and uniform coating, thereby solving the related problems that urgently need to be solved in the prior art. Summary of the invention
[0006] The first aspect of the present invention provides a method for preparing a modified perfluoroethylene propylene copolymer composition, the method comprising: mixing a first perfluoroethylene propylene copolymer dispersion, a second perfluoroethylene propylene copolymer dispersion and a polyurethane dispersion to form the modified perfluoroethylene propylene copolymer composition; wherein the first perfluoroethylene propylene copolymer dispersion comprises first perfluoroethylene propylene copolymer particles having an average particle size of less than 100 nanometers, and the second perfluoroethylene propylene copolymer dispersion comprises second perfluoroethylene propylene copolymer particles having an average particle size of 100 nanometers to 400 nanometers.
[0007] According to one embodiment of the first aspect of the present application, based on the total weight of the modified perfluoroethylene-propylene copolymer composition as 100 weight %, the content of the first perfluoroethylene-propylene copolymer dispersion is 2-20 weight %. According to another embodiment of the first aspect of the present application, based on the total weight of the modified perfluoroethylene-propylene copolymer composition as 100 weight %, the content of the second perfluoroethylene-propylene copolymer dispersion is 75-95 weight %. According to another embodiment of the first aspect of the present application, based on the total weight of the modified perfluoroethylene-propylene copolymer composition as 100 weight %, the content of the polyurethane dispersion is 0.1-5 weight %.
[0008] According to another embodiment of the first aspect of the present application, the solid content of the first perfluoroethylene propylene copolymer dispersion is 50-65 wt %, contains 6-15 wt % of at least one first surfactant, and the first perfluoroethylene propylene copolymer dispersion contains first perfluoroethylene propylene copolymer microparticles with an average particle size of 30-90 nanometers.
[0009] According to another embodiment of the first aspect of the present application, the second perfluoroethylene propylene copolymer dispersion has a solid content of 45-55 wt%, contains 2-8 wt% of at least one second surfactant, and the second perfluoroethylene propylene copolymer dispersion contains second perfluoroethylene propylene copolymer microparticles with an average particle size of 150-300 nanometers.
[0010] According to another embodiment of the first aspect of the present application, the polyurethane dispersion contains 20-30 wt % of polyurethane particles having an average particle size of 2-50 nanometers.
[0011] According to another embodiment of the first aspect of the present application, the molecular weight of the first perfluoroethylene propylene copolymer contained in the first perfluoroethylene propylene copolymer dispersion is 150,000 to 400,000. According to another embodiment of the first aspect of the present application, the molecular weight of the second perfluoroethylene propylene copolymer contained in the second perfluoroethylene propylene copolymer dispersion is 300,000 to 700,000. According to another embodiment of the first aspect of the present application, the molecular weight of the polyurethane contained in the polyurethane dispersion is 30,000 to 150,000.
[0012] The second aspect of the present invention provides a modified perfluoroethylene propylene copolymer composition, which comprises first perfluoroethylene propylene copolymer particles, second perfluoroethylene propylene copolymer particles and polyurethane particles; the particle size of the first perfluoroethylene propylene copolymer particles is less than 100 nanometers, and the particle size of the second perfluoroethylene propylene copolymer particles is 100-400 nanometers; based on 100 parts by weight of the second perfluoroethylene propylene copolymer particles, the content of the first perfluoroethylene propylene copolymer particles is 3-25 parts by weight, and the content of the polyurethane particles is 0.01-6 parts by weight.
[0013] According to one embodiment of the second aspect of the present application, the composition is prepared by the method described in any one embodiment of the first aspect.
[0014] The third aspect of the present invention provides an adhesive or a coating comprising the modified perfluoroethylene-propylene copolymer composition according to the second aspect of the present invention.
[0015] The fourth aspect of the present invention provides a laminate comprising at least one polyimide layer and at least one perfluoroethylene propylene copolymer layer, wherein the polyimide layer is in direct contact with the perfluoroethylene propylene copolymer layer, and the perfluoroethylene propylene copolymer layer is prepared using the adhesive or coating described in the third aspect of the present invention.
[0016] In the following detailed description section, the process and design of the present application are described in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A schematic diagram showing a laminate manufactured according to one embodiment of the present application, wherein a modified FEP coating is applied to both side surfaces of a polyimide film;
[0018] Figure 2A and Figure 2B The SEM images of the cross sections of the modified FEP coatings prepared in Example 1 and Example 2 of the present invention are shown respectively, Figure 2C and Figure 2D The SEM images of the cross sections of the FEP coatings prepared in Comparative Example 1 and Comparative Example 2 are shown respectively;
[0019] Figure 3 The tensile force-deformation curve of the modified FEP composition prepared in Example 1 of the present invention during the tensile strength test is shown. DETAILED DESCRIPTION
[0020] "Range" disclosed herein is in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundary of a particular range. All ranges that can be defined in this way are inclusive of end values and combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, a range of 60-120 and 80-110 is listed for a particular parameter, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.
[0021] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this document, and "0-5" is just an abbreviation of these numerical combinations.
[0022] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0023] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0024] In the present invention, if there is no special explanation, the "including" mentioned herein means open or closed. For example, the "including" may mean that other components not listed may also be included, or only the listed components may be included.
[0025] It should be emphasized that what is shown in the drawings and described below are only some specific embodiments of the present invention, and the protection scope of the present invention is not limited to these specific embodiments. The protection scope of the present invention is defined by the claims of the present invention, and may include any technical solution within the scope of the claims, including but not limited to further improvements and substitutions to these specific embodiments.
[0026] In the following description, perfluoroethylene propylene copolymer and FEP are used interchangeably, and polyimide and PI are used interchangeably.
[0027] The invention of the present application is to modify a conventional FEP dispersion (e.g., emulsion) by a simple and low-cost process and raw materials to obtain a modified FEP composition with excellent stability and applicability-film-forming properties. The composition is particularly suitable for application as a coating or adhesive to polyimide films or sheets, achieving an extremely excellent FEP film layer and significantly improved bonding strength.
[0028] The method for preparing the modified FEP composition of the present invention comprises mixing a first FEP dispersion, a second FEP dispersion and a polyurethane dispersion to form the modified FEP composition. In the present invention, the so-called "modification" means that the performance of the FEP dispersion is improved and enhanced by mixing the above-mentioned selected specific components.
[0029] According to one embodiment of the present application, the first FEP dispersion is an emulsion, preferably an aqueous emulsion, which comprises first FEP particles dispersed in an aqueous solvent (preferably water). According to another embodiment of the present application, the average particle size of the FEP particles contained in the first FEP dispersion is less than 100 nanometers, for example, 10-90 nanometers, more preferably 30-50 nanometers.
[0030] According to one embodiment of the present application, the mass ratio of tetrafluoroethylene to hexafluoropropylene (TFE:HFP mass ratio) contained in the FEP polymer in the first FEP dispersion is 75:25 to 90:10, or 76:24 to 85:15, or 78:22 to 80:20.
[0031] According to one embodiment of the present application, the molecular weight of the FEP particles contained in the first FEP dispersion is 150,000 to 400,000, for example, 200,000 to 300,000.
[0032] In the present invention, the molecular weight of various polymer materials is the weight average molecular weight, which can be calculated by measuring the melt index of the polymer according to the following formula:
[0033]
[0034] Wherein Mv=53150 / MFR, MFR is the measured melt index.
[0035] According to another embodiment of the present application, based on the total weight of the first FEP dispersion, the solid content of the first FEP dispersion is 50-65% by weight, preferably 55-63% by weight, and more preferably 59-61% by weight. According to one embodiment of the present application, the first FEP dispersion is an emulsion, which is prepared by the conventional emulsion polymerization method of the present application, or further concentrated after the emulsion polymerization method to concentrate the FEP emulsion to the above concentration range.
[0036] According to another embodiment of the present application, based on the total weight of the first FEP dispersion, the first FEP dispersion contains 6-15 wt% of the first emulsifier, preferably 8-13 wt%, more preferably 10-12 wt%. According to one embodiment of the present application, the first emulsifier is the emulsifier added during the preparation of the first FEP dispersion (e.g., the first FEP emulsion) by emulsion polymerization and / or during the subsequent concentration process.
[0037] According to one embodiment of the present application, the second FEP dispersion is an emulsion, preferably an aqueous emulsion, which comprises second FEP particles dispersed in an aqueous solvent (preferably water). According to another embodiment of the present application, the average particle size of the FEP particles contained in the second FEP dispersion is ≥100 nanometers, for example, 100-400 nanometers, preferably 150-300 nanometers, more preferably 180-250 nanometers, and most preferably 200-210 nanometers.
[0038] According to one embodiment of the present application, the FEP polymer in the second FEP dispersion comprises a molar ratio of tetrafluoroethylene to hexafluoropropylene (TFE:HFP molar ratio) of 76:24 to 95:15, or 80:20 to 90:10, or 82:18 to 85:15.
[0039] According to one embodiment of the present application, the molecular weight of the FEP particles contained in the second FEP dispersion is 300,000 to 700,000, or 400,000 to 600,000, or 450,000 to 550,000, preferably about 500,000.
[0040] According to another embodiment of the present application, based on the total weight of the second FEP dispersion, the solid content of the second FEP dispersion is 45-55% by weight, preferably 48-53% by weight, and more preferably 49-51% by weight. According to one embodiment of the present application, the second FEP dispersion is an emulsion, which is prepared by the conventional emulsion polymerization method of the present application, or further concentrated after the emulsion polymerization method to concentrate the FEP emulsion to the above concentration range.
[0041] According to another embodiment of the present application, based on the total weight of the second FEP dispersion, the second FEP dispersion contains 2-8 wt% of the second emulsifier, preferably 3-7 wt%, more preferably 4-6 wt%, and most preferably 5-5.5 wt%. According to one embodiment of the present application, the second emulsifier is the emulsifier added in the preparation process by emulsion polymerization and / or in the subsequent emulsion concentration process.
[0042] According to an exemplary embodiment of the present application, the first FEP dispersion and the second FEP dispersion are prepared by the following emulsion polymerization process: water, an emulsifier and an initiator (e.g., a free radical initiator) are added to an emulsion polymerization reactor, and other reagents such as a chain extender, a chain transfer agent, a stabilizer, etc. can be optionally added to the reactor as needed. Then, the monomers tetrafluoroethylene and hexafluoropropylene gas are mixed and charged into the emulsion polymerization reactor, and the polymerization reaction is carried out at the desired reaction temperature and pressure. Optionally, monomers and / or other reagents can be added to the reactor in a continuous or intermittent manner as needed during the polymerization reaction. The finally formed particulate FEP particles are dispersed in water to form a FEP light emulsion product. By adjusting the process conditions and the amount of various reactants / reagents, the formed FEP particles have the desired average particle size. The above-mentioned emulsion polymerization reaction and the means for adjusting the particle size are known to those of ordinary skill in the art. The solid content of the formed FEP light emulsion is usually 20-30% by weight, and then it can be concentrated to the desired concentration using conventional concentration techniques in the art as needed, for example, the first FEP light emulsion with a smaller particle size is concentrated to a solid content of 50-65% by weight as the first FEP dispersion described above; and the second FEP light emulsion with a larger particle size is concentrated to a solid content of 45-55% by weight as the second FEP dispersion described above.
[0043] According to an exemplary embodiment of the present application, the FEP light emulsion prepared by the emulsion polymerization method can be concentrated into a concentrated solution with a desired solid content by a “cloud point concentration method”.
[0044] According to a specific embodiment of the present application, the concentration method can be carried out in the following manner: the FEP light emulsion is heated to a specific temperature (slightly higher than the cloud point), and then a "concentrating emulsifier" is added thereto, and the light emulsion and the emulsifier are fully mixed and contacted by stirring. At this time, the temperature is lowered, and the stirring is stopped. After standing, the above mixture is separated into two layers, the upper layer is a clear layer, and the lower layer is a turbid layer. The upper clear layer is removed by decantation or (using a dropper or pipette) pipetting, and the lower mixed layer is a concentrated FEP emulsion (the first FEP dispersion or the second FEP dispersion) having the concentration of the FEP dispersion described above.
[0045] According to an exemplary embodiment of the present application, the first emulsifier and the second emulsifier are independently selected from one or more of the following: polyether polyol emulsifiers (such as polyethylene glycol, castor oil polyoxyalkylene ether, ethylene oxide-propylene oxide block copolymer, polyvinyl alcohol, perfluoropolyether), ester emulsifiers (such as polyol fatty acid esters, more specifically pentaerythritol fatty acid esters, glycerol fatty acid esters, Tween emulsifiers, Span emulsifiers, etc.), alcohol amine emulsifiers (such as isopropanolamine), fatty alcohol sulfates, fatty alcohol xanthate esters, fatty acid alkali metal salts or ammonium salts, alkali metal salts or ammonium salts of fluorinated (such as perfluorinated) fatty acids, etc.
[0046] According to another embodiment of the present application, the "emulsifier for concentration" used in the cloud point concentration method described above is a nonionic emulsifier, examples of which include nonylphenol polyoxyethylene ether, such as NP-10; and polyoxyethylene ethers, such as TMN-6, TMN-10, and isomeric tridecanol polyoxyethylene ether.
[0047] According to one embodiment of the application, the polyurethane dispersion used is an emulsion, suspension or solution formed by polyurethane microparticles dispersed in water. Based on the gross weight of the polyurethane dispersion, the solid content thereof is 20-30% by weight, preferably 25-30% by weight. According to another embodiment of the application, the average particle diameter of the polyurethane microparticles in the polyurethane dispersion is 2-50 nanometers, preferably 30-40 nanometers. The polyurethane dispersion can be prepared by methods known in the art, such as suspension method or emulsion method, so that polyisocyanate or oligomeric polyisocyanate raw materials react with isocyanate-active reactants (such as polyols, alkylene oxide compounds, polymerized polyols, etc.)
[0048] According to one embodiment of the present application, the molecular weight of the polyurethane contained in the polyurethane dispersion is 30,000 to 150,000, preferably 50,000 to 100,000, and more preferably 80,000 to 90,000.
[0049] According to one embodiment of the present application, based on the total weight of the modified perfluoroethylene propylene copolymer composition as 100 weight %, the content of the first perfluoroethylene propylene copolymer dispersion is 2-20 weight %, preferably 5-15 weight %, more preferably 7-12 weight %, or 6-8 weight %, or 10-14 weight %.
[0050] According to one embodiment of the present application, based on the total weight of the modified perfluoroethylene propylene copolymer composition as 100 weight %, the content of the second perfluoroethylene propylene copolymer dispersion is 75-95 weight %, preferably 80-94 weight %, more preferably 85-93 weight %, or 91-92 weight %, or 86-88 weight %.
[0051] According to one embodiment of the present application, based on the total weight of the modified perfluoroethylene propylene copolymer composition as 100 weight %, the content of the polyurethane dispersion is 0.1-5 weight %, preferably 0.3-2 weight %, more preferably 0.5-1 weight %, or 0.6-0.7 weight %, or 0.9-1.1 weight %.
[0052] In the present invention, the relative ratio and concentration of the first FEP particles (having a smaller average particle size), the second FEP particles (having a larger average particle size) and the polyurethane particles in the modified FEP composition finally prepared are controlled by designing the ratio and solid content of the first FEP dispersion, the second FEP dispersion and the polyurethane dispersion in the above mixing process.
[0053] The modified FEP composition of the present invention can be used directly as a coating or adhesive, or can be used as a coating or adhesive after adjusting the concentration (adding a solvent thereto or removing the solvent by further concentration) and adding other additional agents (such as weathering agents, fungicides, pigments, adhesion promoters, etc.) as needed. The modified FEP composition of the present invention can be particularly suitable for application to the surface of a polyimide substrate (such as a polyimide film or a polyimide sheet) to obtain Figure 1 The FEP / PI / FEP laminate with modified FEP coatings applied on both sides shown; or applied between two or more polyimide substrates to form, for example, PI / FEP / PI or FEP / PI / FEP / PI / FEP laminates. In these laminates, the FEP coating or adhesive layer is an extremely uniform layer with excellent bonding strength. In addition, the modified FEP composition prepared by the present invention has excellent stability and can be stored for a long time without flocculation or precipitation.
[0054] According to one embodiment of the present application, the method of applying the FEP coating on at least one surface of the PI substrate is selected from: dip coating, blade coating, curtain coating, cast coating, etc. After application, the wet film is dried at a temperature of 100-150° C. to remove moisture from the wet film. The dried coating film is then sintered, for example, at a temperature of 250-380° C.
[0055] After sintering, the laminate is subjected to the required subsequent processing, such as destaticization, edge trimming, cutting to a desired size, winding into a coil, etc.
[0056] The method of the present application is specifically described in the following examples, the purpose of which is to provide a better understanding of the content of the present application. It should be understood that these examples are merely illustrative and not restrictive.
[0057] Example
[0058] The water used in the following examples is deionized water; the second FEP emulsion used is provided by Changshu Sanaifu Zhenfu New Materials Co., Ltd., with a trade name of FR463, a molecular weight of about 500,000, a solid content of 50% by weight, an average particle size of the FEP particles in the emulsion of about 205 nanometers, a surfactant content of about 5.5% by weight, and an appearance of a white translucent emulsion; the polyurethane emulsion used in the examples is provided by Guangdong Yinyang Environmental Protection New Materials Co., Ltd., with a molecular weight of about 80,000, a solid content of 30% by weight, and an average particle size of 40 nanometers; the polyimide film used in the examples is provided by Changshu Zhongxun Aerospace Insulation Materials Co., Ltd., with a product name of polyimide (cast) film, a product model of 6051, and a thickness of 0.1 micrometer; the perfluoropolyether emulsifier used in the synthesis of the first FEP emulsion is provided by Chenguang Boda Company, with a trade name of FSA7050A, and the emulsifier used in the concentration is provided by Shanghai Lingfeng Chemical Company, with a trade name of NP10. The other reagents used are all commercially available analytical reagents and are used directly without further treatment.
[0059] Example 1
[0060] Step 1: In this embodiment, the first FEP emulsion is first synthesized by the following steps: tetrafluoroethylene and hexafluoropropylene are mixed in a raw material mixing container to form a raw material mixture. 40 liters of deionized water and 100 grams of emulsifier are added to a reactor with a volume of 60 liters. The reactor is evacuated, and then the atmosphere in the reactor is replaced with nitrogen. The above evacuation-nitrogen replacement operation is repeated three times, so that the oxygen content in the reactor is less than 30ppm. At this time, 3.5 kg of a raw material mixture of tetrafluoroethylene and hexafluoropropylene (wherein the mass ratio of tetrafluoroethylene to hexafluoropropylene is 25:75) is input into the reactor, and then the temperature in the reactor is raised to 97°C, and 160 grams of an aqueous solution of ammonium persulfate with a concentration of 0.25% by weight is added to the reactor to start the polymerization reaction. During the reaction, the materials in the reactor were continuously stirred, and a raw material mixture of tetrafluoroethylene and hexafluoropropylene (wherein the mass ratio of tetrafluoroethylene to hexafluoropropylene was 80:20) was continuously added to the reactor to keep the pressure in the reactor constant, and an aqueous solution of ammonium persulfate having a concentration of 0.25 wt % was added to the reactor at a flow rate of 10 g / min.
[0061] When the cumulative added mass of the monomer raw material mixture reaches 14 kg, the addition of the monomer raw material and the ammonium persulfate aqueous solution is stopped, the reactor is cooled to room temperature, the unreacted gaseous monomer in the reactor is released, and then the valve at the bottom of the reactor is opened to draw out the material in the reactor to obtain an FEP emulsion with a solid content of about 20 wt % (the first FEP emulsion, also called the first light emulsion).
[0062] The first FEP emulsion was then concentrated by the following steps: 500 g of the first FEP was weighed and placed in a 1-liter beaker, the beaker was placed in a water bath, and the temperature was slowly raised to 65°C while continuously stirring. 30 g of emulsifier NP10 was weighed and slowly added to the 65°C emulsion, and the mixture was fully stirred to mix and contact. After continuous stirring for about 1 hour, the water bath heating was stopped, and the temperature of the emulsion was allowed to drop to 62°C, and then the stirring was stopped and the mixture was allowed to stand for about 1 hour. After the emulsion was separated and the temperature dropped to room temperature, the supernatant was carefully poured out to obtain a bottom concentrated solution with a solid content of 60% by weight, thereby completing the concentration process. The concentrated solution obtained here was used as the first concentrated FEP emulsion in the subsequent steps.
[0063] The average particle size of the particles in the first concentrated FEP emulsion was measured by Malvern's laser particle size analyzer to be 30 nanometers, the molecular weight of the FEP polymer was 200,000, the content of the surfactant (emulsifier used above) was 12% by weight, and the pH of the emulsion was 7.
[0064] Step 2: In this step, the first concentrated FEP emulsion synthesized in step 1, the commercially purchased second FEP emulsion and the polyurethane emulsion are fully mixed in a weight ratio of 7:1:92 to prepare a modified FEP composition.
[0065] Step 3: In the third step, the modified FEP composition prepared in step 2 is applied on both sides of the PI film, and the PI film is cut into 20 cm*2 cm strips; after two strips of the same size are overlapped together, the overlapping portion of 10*2 cm is placed on a flat vulcanizer, and after the strips are dried on both sides, the strips are removed and placed on a tensile tester to test the peel strength. The measured tensile force-deformation defect diagram is shown in FIG. Figure 3 As shown. The adhesion between PI films was thus detected.
[0066] In addition, the modified FEP composition prepared in step 2 was applied on both sides of the PI film, the PI film and the copper sheet were cut into 20*2 cm strips, the polyimide film and the copper sheet of the same size were overlapped, and the overlapping portion of 10*2 cm was placed on a flat vulcanizer, and the strips were heated on both sides, then removed and placed on a tensile tester to test the peel strength, thereby testing the bonding strength between the PI and the copper sheet.
[0067] Use SEM to check the quality of FEP coating cross section, such as Figure 2A It can be seen that the modified FEP composition of the present invention can form a uniform and dense coating.
[0068] In addition, the FEP composition prepared in this example was placed under ambient conditions for one month to evaluate its stability.
[0069] Example 2
[0070] Step 1: In this embodiment, the first FEP emulsion is first synthesized by the following steps: tetrafluoroethylene and hexafluoropropylene are mixed in a raw material mixing container to form a raw material mixture. 40 liters of deionized water, 50 grams of perfluoropolyether emulsifier and 50 grams of perfluorodioxyheptacarbonic acid are added to a reactor with a volume of 60 liters. The reactor is evacuated, and then the atmosphere in the reactor is replaced with nitrogen. The above vacuum-nitrogen replacement operation is repeated three times, so that the oxygen content in the reactor is less than 30ppm. At this time, 3.5 kg of a raw material mixture of tetrafluoroethylene and hexafluoropropylene (wherein the mass ratio of tetrafluoroethylene to hexafluoropropylene is 25:75) is input into the reactor, and then the temperature in the reactor is raised to 97°C, and 100 grams of an aqueous solution of ammonium persulfate with a concentration of 0.25% by weight is added to the reactor to start the polymerization reaction. During the reaction, the materials in the reactor were continuously stirred, and a raw material mixture of tetrafluoroethylene and hexafluoropropylene (wherein the mass ratio of tetrafluoroethylene to hexafluoropropylene was 90:10) was continuously added to the reactor to keep the pressure in the reactor constant, and an aqueous solution of ammonium persulfate having a concentration of 0.25 wt % was added to the reactor at a flow rate of 6 g / min.
[0071] When the cumulative added mass of the monomer raw material mixture reaches 14 kg, the addition of the monomer raw material and the ammonium persulfate aqueous solution is stopped, the reactor is cooled to room temperature, the unreacted gaseous monomer in the reactor is released, and then the valve at the bottom of the reactor is opened to draw out the material in the reactor to obtain an FEP emulsion with a solid content of about 20 wt % (the first FEP emulsion, also called the first light emulsion).
[0072] The first FEP emulsion was then concentrated by the following steps: 500 g of the first FEP was weighed and placed in a 1-liter beaker, the beaker was placed in a water bath, and the temperature was slowly raised to 65°C while continuously stirring. 30 g of emulsifier NP10 was weighed and slowly added to the 65°C emulsion, and the mixture was fully stirred to mix and contact. After continuous stirring for about 1 hour, the water bath heating was stopped, and the temperature of the emulsion was allowed to drop to 62°C, and then the stirring was stopped and the mixture was allowed to stand for about 1 hour. After the emulsion was separated and the temperature dropped to room temperature, the supernatant was carefully poured out to obtain a bottom concentrated solution with a solid content of 60% by weight, thereby completing the concentration process. The concentrated solution obtained here was used as the first concentrated FEP emulsion in the subsequent steps.
[0073] The average particle size of the particles in the first concentrated FEP emulsion was measured to be 50 nanometers, the molecular weight of the FEP polymer was 200,000, the content of the surfactant (emulsifier used above) was 12% by weight, and the pH of the emulsion was 7.
[0074] Step 2: In this step, the first concentrated FEP emulsion synthesized in step 1, the commercially purchased second FEP emulsion and the polyurethane emulsion are fully mixed in a weight ratio of 12:0.5:87.5 to prepare a modified FEP composition.
[0075] Step 3: The adhesion between the PI film layers and the adhesion between the PI film and the copper sheet are tested in the same steps as in Example 1.
[0076] Use SEM to check the quality of FEP coating cross section, such as Figure 2B It can be seen that the modified FEP composition of the present invention can form a uniform and dense coating.
[0077] In addition, the FEP composition prepared in this example was placed under ambient conditions for one month to evaluate its stability.
[0078] Comparative Example 1
[0079] In this comparative example 1, a commercially available second FEP emulsion was directly used as an adhesive and applied to the PI film. The adhesion between the PI film layers and the adhesion between the PI film and the copper sheet were tested according to the same steps as in Example 1.
[0080] Use SEM to check the quality of FEP coating cross section, such as Figure 2C It can be seen that a coating can be obtained using the FEP emulsion, but the uniformity of the coating is not as good as that of the coatings in Examples 1 and 2, and a small amount of defects can be observed in the coating interface.
[0081] In addition, the FEP composition prepared in this comparative example was placed under ambient conditions for one month to evaluate its stability.
[0082] Comparative Example 2
[0083] In this comparative example, an FEP emulsion with an average particle size of about 120 nanometers was synthesized and used as the first FEP emulsion raw material to prepare a modified FEP composition in the same manner as in Example 1, and its properties were characterized.
[0084] Step 1: In this comparative example, a first FEP emulsion having a relatively large average particle size (greater than 100 nanometers) is first synthesized by the following steps: tetrafluoroethylene and hexafluoropropylene are mixed in a raw material mixing container to form a raw material mixture. 40 liters of deionized water, 10 grams of perfluoropolyether emulsifier and 90 grams of perfluorodioxyheptacarbonic acid are added to a reactor with a volume of 60 liters. The reactor is evacuated, and then the atmosphere in the reactor is replaced with nitrogen. The above evacuation-nitrogen replacement operation is repeated three times, so that the oxygen content in the reactor is less than 30 ppm. At this time, 3.5 kg of a raw material mixture of tetrafluoroethylene and hexafluoropropylene (wherein the mass ratio of tetrafluoroethylene to hexafluoropropylene is 25:75) is input into the reactor, and then the temperature in the reactor is raised to 97°C, and 160 grams of an aqueous solution of ammonium persulfate with a concentration of 0.25% by weight is added to the reactor to start the polymerization reaction. During the reaction, the materials in the reactor were continuously stirred, and a raw material mixture of tetrafluoroethylene and hexafluoropropylene (wherein the mass ratio of tetrafluoroethylene to hexafluoropropylene was 80:20) was continuously added to the reactor to keep the pressure in the reactor constant, and an aqueous solution of ammonium persulfate having a concentration of 0.25 wt % was added to the reactor at a flow rate of 10 g / min.
[0085] When the cumulative added mass of the monomer raw material mixture reaches 14 kg, the addition of the monomer raw material and the ammonium persulfate aqueous solution is stopped, the reactor is cooled to room temperature, the unreacted gaseous monomer in the reactor is released, and then the valve at the bottom of the reactor is opened to draw out the material in the reactor to obtain an FEP emulsion with a solid content of about 20 wt % (the first FEP emulsion, also called the first light emulsion).
[0086] The first FEP emulsion was then concentrated by the following steps: 500 g of the first FEP was weighed and placed in a 1-liter beaker, the beaker was placed in a water bath, and the temperature was slowly raised to 65°C while continuously stirring. 30 g of emulsifier NP10 was weighed and slowly added to the 65°C emulsion, and the mixture was fully stirred to mix and contact. After continuous stirring for about 1 hour, the water bath heating was stopped, and the temperature of the emulsion was allowed to drop to 62°C, and then the stirring was stopped and the mixture was allowed to stand for about 1 hour. After the emulsion was separated and the temperature dropped to room temperature, the supernatant was carefully poured out to obtain a bottom concentrated solution with a solid content of 60% by weight, thereby completing the concentration process. The concentrated solution obtained here was used as the first concentrated FEP emulsion in the subsequent steps.
[0087] The average particle size of the particles in the first concentrated FEP emulsion was measured to be 120 nanometers, the molecular weight of the FEP polymer was 200,000, the content of the surfactant (emulsifier used above) was 12% by weight, and the pH of the emulsion was 7.
[0088] Step 2: In this step, the first FEP emulsion synthesized in step 1, the commercially purchased second FEP emulsion and the polyurethane emulsion are fully mixed in a weight ratio of 7:1:92 to prepare a modified FEP composition.
[0089] Step 3: The adhesion between the PI film layers and the adhesion between the PI film and the copper sheet are tested in the same steps as in Example 1.
[0090] Use SEM to check the quality of FEP coating cross section, such as Figure 2D It can be seen that a coating can be obtained using the FEP emulsion, but the uniformity of the coating is not as good as that of the coatings in Examples 1 and 2, and a small amount of defects can be observed in the coating interface.
[0091] In addition, the FEP composition prepared in this comparative example was placed under ambient conditions for one month to evaluate its stability.
[0092] Table 1: Characterization results of bonding strength between FEP film and PI film of Example 1-2 and Comparative Example 1-2
[0093]
[0094] It can be seen from Table 1 above that the film-forming properties of Examples 1 and 2 are significantly better than those of Comparative Examples 1 and 2, and the bonding properties between the FEP film and the PI film are also significantly better than those of Comparative Examples 1 and 2.
[0095] Table 2: Characterization results of the bonding performance between the FEP film of Examples 1-2 and Comparative Examples 1-2 and the copper sheet
[0096] sample Adhesion strength between FEP film and copper sheet (N / cm) Example 1 7.00 Example 2 6.67 Comparative Example 1 4.63 Comparative Example 2 5.15
[0097] It can be seen from Table 2 above that the bonding performance of the FEP compositions of Examples 1 and 2 to the copper sheet is significantly better than that of Comparative Examples 1 and 2.
[0098] Table 3: Stability of the modified FEP compositions of Examples 1-2 and Comparative Examples 1-2 after one month of storage
[0099]
[0100] The modified FEP compositions prepared in the above Examples 1-2 and Comparative Examples 1-2 were stored at room temperature for one month, and then the changes in their various properties were detected, wherein the solid content was measured using a densitometer; the "stability" was detected in the following manner: mechanical stirring was performed at 38° C. for 40 hours, and then whether stratification or precipitation occurred was observed.
[0101] As can be seen from Table 3 above, after the FEP compositions of Examples 1 and 2 were stored at room temperature for 30 days, the density and solid content did not change significantly, and no stratification and precipitation occurred, showing excellent storage stability. In sharp contrast, after the same storage time, the density and solid content of Comparative Examples 1 and 2 changed significantly, and precipitation formation was observed.
Claims
1. A method for preparing a modified perfluoroethylene propylene copolymer composition, the method comprising: mixing a first perfluoroethylene propylene copolymer dispersion, a second perfluoroethylene propylene copolymer dispersion and a polyurethane dispersion to form the modified perfluoroethylene propylene copolymer composition; The first perfluoroethylene-propylene copolymer dispersion comprises first perfluoroethylene-propylene copolymer particles having an average particle size of less than 100 nanometers, and the second perfluoroethylene-propylene copolymer dispersion comprises second perfluoroethylene-propylene copolymer particles having an average particle size of 100 nanometers to 400 nanometers.
2. The method according to claim 1, characterized in that Based on 100 wt% of the total weight of the modified perfluoroethylene propylene copolymer composition, the content of the first perfluoroethylene propylene copolymer dispersion is 2-20 wt%, the content of the second perfluoroethylene propylene copolymer dispersion is 75-95 wt%, and the content of the polyurethane dispersion is 0.1-5 wt%.
3. The method according to claim 1, characterized in that The first perfluoroethylene propylene copolymer dispersion has a solid content of 50-65 wt %, contains 6-15 wt % of at least one first surfactant, and contains first perfluoroethylene propylene copolymer microparticles with an average particle size of 30-90 nm.
4. The method according to claim 1, characterized in that The second perfluoroethylene propylene copolymer dispersion has a solid content of 45-55 wt %, contains 2-8 wt % of at least one second surfactant, and contains second perfluoroethylene propylene copolymer microparticles having an average particle size of 150-300 nm.
5. The method according to claim 1, characterized in that The polyurethane dispersion contains 20-30% by weight of polyurethane particles with an average particle size of 2-50 nanometers.
6. The method according to claim 1, characterized in that The molecular weight of the first perfluoroethylene propylene copolymer contained in the first perfluoroethylene propylene copolymer dispersion is 150,000 to 400,000; The molecular weight of the second perfluoroethylene propylene copolymer contained in the second perfluoroethylene propylene copolymer dispersion is 300,000 to 700,000; The molecular weight of the polyurethane contained in the polyurethane dispersion is 30,000 to 150,000.
7. A modified perfluoroethylene propylene copolymer composition, the composition comprising first perfluoroethylene propylene copolymer particles, second perfluoroethylene propylene copolymer particles and polyurethane particles; The particle size of the first perfluoroethylene-propylene copolymer particles is less than 100 nanometers, and the particle size of the second perfluoroethylene-propylene copolymer particles is 100-400 nanometers; Based on 100 parts by weight of the second perfluoroethylene-propylene copolymer particles, the content of the first perfluoroethylene-propylene copolymer particles is 3-25 parts by weight, and the content of the polyurethane particles is 0.01-6 parts by weight.
8. The composition of claim 7, prepared by the method of any one of claims 1-6.
9. An adhesive or a coating comprising the modified perfluoroethylene-propylene copolymer composition according to claim 7 or 8.
10. A laminate comprising at least one polyimide layer and at least one perfluoroethylene propylene copolymer layer, wherein the polyimide layer is in direct contact with the perfluoroethylene propylene copolymer layer, and the perfluoroethylene propylene copolymer layer is prepared using the adhesive or coating according to claim 9.